Conditioned medium from hypoxic bone marrow-derived mesenchymal stem cells enhances wound healing in mice. - Lei Chen; Yingbin Xu; Jingling Zhao; Zhaoqiang Zhang; Ronghua Yang; Julin Xie; Xusheng Liu; Shaohai Qi (PLoS ONE)
Growing evidence indicates that bone marrow-derived mesenchymal stem cells (BM-MSCs) enhance wound repair via paracrine. Because the extent of environmental oxygenation affects the innate characteristics of BM-MSCs, including their stemness and migration capacity, the current study set out to elucidate and compare the impact of normoxic and hypoxic cell-culture conditions on the expression and secretion of BM-MSC-derived paracrine molecules (e.g., cytokines, growth factors and chemokines) that hypothetically contribute to cutaneous wound healing in vivo. Semi-quantitative reverse transcriptase polymerase chain reaction (RT-PCR) and enzyme-linked immunosorbent assay (ELISA) analyses of normoxic and hypoxic BM-MSCs and their conditioned medium fractions showed that the stem cells expressed and secreted significantly higher amounts of basic fibroblast growth factor (bFGF),vascular endothelial growth factor A (VEGF-A) interleukin 6 (IL-6) and interleukin 8 (IL-8) under hypoxic conditions. Moreover, hypoxic BM-MSC-derived conditioned medium (hypoCM) vs. normoxic BM-MSC-derived conditioned medium (norCM) or vehicle control medium significantly enhanced the proliferation of keratinocytes, fibroblasts and endothelial cells, the migration of keratinocytes, fibroblasts, endothelial cells and monocytes, and the formation of tubular structures by endothelial cells cultured on Matrigel matrix. Consistent with these in vitro results, skin wound contraction was significantly accelerated in Balb/c nude mice treated with topical hypoCM relative to norCM or the vehicle control. Notably increased in vivo cell proliferation, neovascularization as well as recruitment of inflammatory macrophages and evidently decreased collagen I, and collagen III were also found in the hypoCM-treated group. These findings suggest that BM-MSCs promote murine skin wound healing via hypoxia-enhanced paracrine.